ANALISIS PERBEDAAN KEMAMPUAN MATEMATIKA BERBASIS 5C (CRITICAL THINKING, CREATIVITY, COMMUNICATION, COLLABORATION, DAN CHARACTER) PADA MAHASISWA DARI BERBAGAI FAKULTAS DI UNIVERSITAS RIAU - Maria Ulfa; Suci Amalia Rambe; Elfi Anisa; Wulan Rahma Dewi; Jesi Alexander Alim (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2025)
This study aims to compare 5C (Character) mathematics skills among students from various faculties at the University of Riau. 5C skills include Critical Thinking, Creativity, Communication, Collaboration, and Character, which are important aspects in modern mathematics learning. The research method used is a quantitative approach with survey techniques and mathematics skills tests as the main instruments. The research sample consisted of 60 students from the faculties of FKIP, FEB, and FMIPA. Data were analyzed using the Rasch Model to evaluate the reliability of the instrument, the level of difficulty of the questions, and the abilities of the students. The results of the analysis showed significant differences in the mastery of 5C mathematics skills between faculties. This study is expected to provide insight into the development of a more effective curriculum and learning strategies in improving students' mathematics skills.